Changing times in the middle of East and West: cultural dispositions three years later - Pilotti, Maura A. E.; Waked, Arifi N. M.; El Alaoui, Khadija; Abdelsalam, Hanadi (Frontiers in Education, 2023)
In the middle of East and West, Saudi Arabia is a society that has been the object of a socioeconomic plan to engineer a sustainable, knowledge-driven, and market-based economy since before the pandemic. The plan, which heavily relies on young college-educated women, requires a traditional collectivistic ethos to adjust to an individualistic one. The pandemic has temporarily interrupted the execution of the plan. The main aim of the present study is two-fold: (a) determine whether female college students' cultural dispositions and conceptual organization habits (similarity-driven versus function-driven ways of organizing information) have changed after the pandemic, and (b) assess whether dispositions and habits contribute to academic attainment (as measured by GPA) differently before and after the pandemic. To this end, through a cross-sectional design, this retrospective study examines the cultural dispositions and conceptual organization habits of a sample of bilingual female college students 3 years apart before and after the pandemic. It finds no differences in conceptual organization habits as a function of time and no relationship between either cultural dispositions or conceptual organization habits and academic attainment. However, horizontal individualism is found to increase after the pandemic as well as to be negatively related to function-driven conceptual organization habits. Although these findings underlie the increasing individualism that accompanies socioeconomic development globally, they question common assumptions of a straightforward link between academic attainment and cultural differences.